Health in rural Sri Lanka: a cross-sectional survey of three rural districts - Senarath, Upul; Senanayake, Sanath; Pathirana, Sisira; Karunaweera, Nadira; Weerasinghe, Manuj C; Gunawardena, Nalika S; Munugoda, Ishanka P; Jayasinghe, Saroj; Amarathunga, Priyani; Corea, Enoka; De Silva, Varuni; Fernando, Deepika; et al. (Ceylon Medical Journal, 2019)
Introduction: Sri Lanka has a predominantly rural population. However, there is a dearth of research on health and socioeconomic issues in this group. Objective: To describe basic socioeconomic characteristics and health profile in a rural population. Methods: A descriptive cross-sectional household survey was conducted in 1950 households in three rural districts, selected by a three-stage stratified cluster sampling method. Results: The population pyramid showed an ageing population (dependency ratio of 50%). Only 39% had completed GCE (ordinary level). Unemployment rates were high (25% males, 76% females). Agriculture and related work were main occupations. Most lacked amenities (e.g. 61% households lacked a refrigerator) and practiced inappropriate methods of waste disposal (e.g. open burning by 72%). Household illnesses were frequent: episodes of acute illness within two weeks, injuries within past year and chronic illness were reported from 35.9%, 14.9% and 48.3% households. The prevalence of chronic diseases in adults >20 years were high: diabetes 13.5%, hypertension 16.7% and overweight/obesity 28.2%. Of the males, 22.1% smoked and 12.3% took alcohol. Almost 25% adults chewed betel. Reports of snake bite, dog bites and suicide/ attempted suicide were seen in 15.5%, 9.7% and 3.0% households respectively. Conclusions: This study shows a unique clustering of health-related problems in rural Sri Lanka. This was characterized by demographic transition, burden from snake bites, chronic diseases and acute illnesses. There were resource limitations and low levels of education. Cohort studies and comparisons with urban areas will enable further elucidation of determinants of health and other issues in rural Sri Lanka.
Keywords: communicable disease; non communicable disease; Sri Lanka; rural; health